2002
DOI: 10.1152/ajpheart.2002.282.1.h264
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nonnoradrenergic cutaneous vasoconstriction in women is associated with reproductive hormone status

Abstract: We tested whether a nonnoradrenergic component of reflex vasoconstriction of skin blood flow (SkBF) is sensitive to female reproductive hormones. Six women taking oral contraceptives underwent whole-body cooling during high-hormone (HH) and low-hormone (LH) phases of oral contraceptive use. SkBF was monitored by laser Doppler flowmetry (LDF) at sites treated by intradermal injection of yohimbine-propranolol (5 mM and 1 mM; YOPR) to block the effects of norepinephrine (NE) or at saline (Sal) control sites. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 54 publications
11
47
2
Order By: Relevance
“…As shown in our previous study, the cutaneous LD flux response to local cooling is importantly influenced by hormonal status even in non-pregnant women [26]. In the present study we found significantly diminished relative LD flux decrease during direct cooling in non-hypertensive pregnant females compared to non-pregnant females.…”
Section: Normotensive Pregnancysupporting
confidence: 82%
See 1 more Smart Citation
“…As shown in our previous study, the cutaneous LD flux response to local cooling is importantly influenced by hormonal status even in non-pregnant women [26]. In the present study we found significantly diminished relative LD flux decrease during direct cooling in non-hypertensive pregnant females compared to non-pregnant females.…”
Section: Normotensive Pregnancysupporting
confidence: 82%
“…After women have reached puberty, their cardiovascular system becomes subjected to a cyclic menstrual variation that involves hormonal status, autonomic nervous system activity, and peripheral vascular reactivity [6,20,26].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous vasoconstrictor responses are mediated directly via norepinephrine but also by coreleased neuromodulators (26,27). Recently, Stephens et al (28) have identified that up to 40% of the cutaneous vasoconstrictor response may be mediated via neuropeptide Y in young subjects during cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the participants were instructed not to eat for 1 h prior to the testing session, but were encouraged to drink water ad libitum. Female participants were all using oral contraceptives and were currently in the lowhormone phase of their routine as verified through selfreport (Charkoudian 2001;Stephens et al 2002). Additionally, recent work has demonstrated no sex differences in the thermal hyperaemia response to local skin heating (Stanhewicz et al 2014).…”
Section: Participantsmentioning
confidence: 97%